Given that f : R → (–1, 1) is defined by
Here for mod function we will consider three cases, x = 0, x<0 and x>0.
For x< 0
⇒ y(1 + x2) = x2
⇒ x2 (1 – y) = y
Also, checking on x>0 and x = 0 we find that
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation